Age of Consent in Islam: Between Legal Principles, Controversies, and Social Adaptations - Qomaro, Galuh Widitya (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2023)
The Age of Consent is a key element in determining the legal and social aspects that regulate the minimum age at which individuals are legally allowed to engage in sexual activities. In some predominantly Muslim countries, there may not be a specifically defined age of consent for sexual activities outside of marriage; instead, the emphasis is on sexual relations within the context of marriage. Traditional factors and religious beliefs often play a significant role in shaping the legal framework governing intimate relationships. This research provides insights into the variations in the age of consent laws and their relationship with marriage in several Muslim-majority countries. The legal principles found in the Quran and Hadith provide a foundational framework that reflects the relevance of Islam for all people in various temporal and geographical contexts, with the principle of preventing harm as a primary basis. Protecting children and vulnerable individuals should always remain a top priority. The issues of age of consent and child marriage are ongoing and require careful consideration, with a focus on the well-being of children and the interests of individuals